Analysis for Three-Dimensional Curved Objects by Runge-Kutta High Order Time-Domain Method - Zhu, Min; Cao, Qunsheng; Zhao, Lei; Wang, Yi (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a Conformal RungeKutta High Order Time Domain (C-RK-HOFDTD) method has been presented and applied to model and analyze in curved objects. The general update equations of the method and the Effective Dielectric Constant (EDC) have been derivated. The scattering of the cylinder and ellipsoid are used to validate the proposed method, and the results are shown that the scheme provides the better accuracy than the HO-FDTD and other higher order methods.